A new genus of the family Theridiidae Sundevall, 1833 (Araneae: Theridiidae) from Asia, with description of a new species - Fang, Yujun; Liu, Jie; Hu, Changhao (Zootaxa, 2026)
Chrosiothes Simon, 1894 (Spintharinae) is a genus of theridiid spiders including 25 American and three Asian species. A detailed comparation shows that the Asian species differ markedly from American Chrosiothes, instead bearing several synapomorphies of the subfamily Theridiinae Sundevall, 1833, in addition to some unusual apomorphic characteristics. Based on these observations, a new genus, Loricatheridion gen. nov., is established to accommodate the three Asian “Chrosiothes” species, and a new species from Hubei, China that is described herein.